1995
DOI: 10.1111/j.1399-0004.1995.tb04063.x
|View full text |Cite
|
Sign up to set email alerts
|

Population frequency of apolipoprotein E5 (Glu3→Lys) and E7 (Glu244→Lys, Glu245→Lys) variants in western Japana

Abstract: Apolipoprotein (apo) E modulates the catabolism of chylomicrons and of very low density lipoprotein remnants. It has three major isoforms (apo E2, E3, E4) and some rare variants. To detect the variants of apo E, blood specimens from 1269 Japanese subjects were analyzed using isoelectric focusing with immunoblotting. The E5 and E7 variants were identified by IEF in 2 and 18 subjects, respectively. Both E5 (Glu3→Lys) carriers were confirmed by PCR‐mediated site‐directed mutagenesis, and all E7 (Glu244→Lys, Glu24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 30 publications
0
16
0
1
Order By: Relevance
“…As shown in Table 2, statins were given in four cases (No. 3,6,10,15), but only one case (No. 23) showed LDL-C levels above 140 mg/dL.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Table 2, statins were given in four cases (No. 3,6,10,15), but only one case (No. 23) showed LDL-C levels above 140 mg/dL.…”
Section: Resultsmentioning
confidence: 99%
“…The ~3 allele is the most common allele in every population. The Japanese population has a low ~2 allele frequency (4.0%) (Matsunaga et al 1995), while the Chinese population has a low ~4 frequency (7.4%) (Hallman et al 1991). Also among Caucasian populations there is a significant variation in the allele frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies have suggested that polymorphism at +2836 G>A of the APOE gene is strongly related to the susceptibility to hypertension; the A allele of the APOE gene may be a risk factor for hypertension in Chinese Hui individuals while the G allele may serve as a protective factor for hypertension. This genetic variation at the +2836 G>A site of the APOE gene was first described by Matsunaga et al [17] who demonstrated that the G>A mutation changed glutamic acid into a lysine residue. Additionally, polymorphisms of the APOE gene have also been correlated with plasma lipid levels and susceptibility to hypertension in a variety of ethnic groups, although there have been inconsistent results [18].…”
Section: Discussionmentioning
confidence: 99%